Aplicación del modelo SERVPERF para la medición de la percepción sobre la calidad del servicio de la educación superior - Farid Luna Pérez (Ecomatemático, 2017)
This paper is based on the application of a methodology used to assess the students’ attitudes to the quality of their higher education in the education service, using the example of students of Economic and Business Sciences from Pamplona University, at the Villa del Rosario campus, using the SERVPERF model. The objective of this inves-tigation is to obtain the information necessary to design and implement policies in favor of the Faculty’s academic processes. The study also aims to outline the SERVPERF model, and thus identify the attitudes to the quality of a given service and its application in everyday life. The SERVPERF model is composed of five (5) dimensions: Relia-bility, Empathy, Responsiveness, Tangibility and Security, of which three (3) showed a higher level of acceptance, and as such were classified as strengths, but in turn two obtained a lower degree of favorability, and were thus grou-ped as weaknesses for the university branch. In general terms, the Villa del Rosario campus was viewed favorably by the students, identifying the Administration of Companies Program as the highest quality program in relation to the service of their education, followed by the Economy and Public Accounting, which always maintained a critical view and unfavorable perception of the university